EFFECT OF GENERAL ALLOCATION FUND, SPECIAL ALLOCATION FUNDS AND CAPITAL EXPENDITURES ON FINANCIAL PERFORMANCE OF REGENCY/CITY GOVERNMENT IN NORTH SUMATRA PROVINCE IN 2013 – 2018 - Husni, Yuanita Larosa (Asosiasi Dosen Akuntansi Indonesia, 2021)
This study aims to determine the effect of general allocation funds, special allocation funds, capital expenditure on financial performance in the North Sumatra Provincial Government. This type of research is causal research. This research is sourced from Local Government Fund (APBD) data and Local Government Fund (APBD) realization reports obtained from data published by the Central Statistics Agency and through the portal of the Directorate General of Fiscal Balance. Sample selection using a saturated sample shows that the study sample is 33 regencies / cities with a period of 6 years of research, so the number of observations in this study is 198 data. The data analysis method used in this study is Panel Data Regression Analysis which was performed with the help of Eviews 9 software. The results showed that general allocation funds and special allocation funds had a significant positive effect on the financial performance of the North Sumatra Province government. While capital expenditure has a significant negative effect on the financial performance of the government of North Sumatra Province.